Pengaruh Biaya Operasional Terhadap Pendapatan Operasional dan Non Performing Financing Terhadap Return On Assets Pada Bank Umum Syariah - Rahmawati, Ayu Nur (COMPETITIVE, 2023)
Before investing, an investor must know what can affect the rate of return on company assets. For this reason, this study intends to see whether there is an effect between Operational Costs on Operating Income and Non-Performing Financing on the Return On Assets of the sample companies. Purposive Sampling method was used in determining the sample with certain criteria so that 40 samples were obtained from selected Islamic Commercial Banks. This study obtained data sources from the Financial Services Authority and the website of each sample bank. ROA is negatively affected by BOPO and positively influenced by NPF, this result is shown from the Partial Test (t test). BOPO and NPF have a simultaneous effect on ROA, this is indicated by the simultaneous test (f test).